Don't cry, Tai Lake - Qiu, Xiaolong, 1953- (Qiu, Xiaolong, 1953- Inspector Chen novel., 2012)
Offered a luxury vacation near Lake Tai, Chief Inspector Chen Cao is drawn into the murder investigation of a manufacturing plant director who had been accused of polluting the once-beautiful lake, a case that implicates the leader of a local ecological group.